2021
DOI: 10.1093/pm/pnaa417
|View full text |Cite
|
Sign up to set email alerts
|

The Resurrection of Interdisciplinary Pain Rehabilitation: Outcomes Across a Veterans Affairs Collaborative

Abstract: Objective Despite empirical support for interdisciplinary pain rehabilitation programs improving functioning and quality of life, access to this treatment approach has decreased dramatically over the last 20 years within the United States but has grown significantly in the Department of Veterans Affairs (VA). Between 2009 and 2019, VA pain rehabilitation programs accredited by the Commission on Accreditation of Rehabilitation Facilities increased 10-fold in the VA, expanding from two to 20. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Recently, a study of 6 IPRPs within the Veteran's Affairs Healthcare System demonstrated a statistically significant reduction in insomnia symptoms at program discharge. 14 Craner et al 11 also documented statistically significant reductions in insomnia severity following IPRP participation. Another study reported that total sleep time increased over the course of IPRP treatment and that improvement in sleep was related to improvement in pain.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, a study of 6 IPRPs within the Veteran's Affairs Healthcare System demonstrated a statistically significant reduction in insomnia symptoms at program discharge. 14 Craner et al 11 also documented statistically significant reductions in insomnia severity following IPRP participation. Another study reported that total sleep time increased over the course of IPRP treatment and that improvement in sleep was related to improvement in pain.…”
Section: Introductionmentioning
confidence: 96%
“…Prior research evaluating the impact of IPRP participation on insomnia symptoms has also yielded mixed results. Recently, a study of 6 IPRPs within the Veteran’s Affairs Healthcare System demonstrated a statistically significant reduction in insomnia symptoms at program discharge 14 . Craner et al 11 also documented statistically significant reductions in insomnia severity following IPRP participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TelePain specialists are physically located in a single VA medical center at one of two divisions (Seattle, WA or Tacoma, WA). TelePain is built on the model of interdisciplinary, team-based pain management [ 15 ]. TelePain’s outpatient rehabilitation-focused services are based on a biopsychosocial model of chronic pain.…”
Section: Methodsmentioning
confidence: 99%
“…These comprehensive, biopsychosocial programs emphasize functional restoration and typically involve physical and occupational therapy, medical visits, and mental health visits. A large body of research supports the claim that IPRPs improve pain, functioning, and quality of life among those with chronic pain ( Craner et al., 2020 ; Gilliam et al., 2018 ; Huffman et al., 2017 ; Murphy et al., 2021 ). IPRPs have also demonstrated significant improvements in insomnia symptoms ( Craner et al., 2020 ).…”
mentioning
confidence: 90%